The butcher's hook - Ellis, Janet (Pegasus Books, 2017)
In the wake of the death of her infant brother in eighteenth-century London, nineteen-year-old Anne Jaccob is determined to marry a butcher's apprentice, no matter what her ailing mother and uncaring father think.